The Implementation of Sinking Illegal Fishing Vessels Policy Towards the Bilateral Relations between Indonesia and Malaysia - Madjid, M. Adnan; Widodo, Widodo; Samudro, Eko G. (Political Science Program, Universitas Negeri Semarang, 2019)
This study discusses the policy implementation by Indonesia regarding the sinking of illegal fishing vessels towards Indonesia's bilateral relations with Malaysia, especially those that occurred in Tarakan and Nunukan. Many losses from illegal fishing by neighboring countries made the President of Indonesia, through the Ministry of Maritime Affairs and Fisheries, took a firm stance regarding the rules of ship sinking to the accused ships that have been proven doing illegal fishing in the Indonesian sea. The Ministry of Maritime Affairs and Fisheries together with relevant agencies helped implement the policy which had an impact on the relationship between Indonesia and Malaysia. In this case, Malaysia is still in third place after Vietnam and the Philippines in the data on the number of vessels destroyed by the Indonesia. Malaysia is also the country with the fifth largest fish commodity production in Southeast Asia whereas fish consumption in Malaysia is ranked first in the region. Thus, the country faces obstacles in fulfilling the need for fish faced with Indonesian policies in addressing illegal fishing arrests by foreign countries. By qualitative methods, this research reveals the background of the existence and implementation of policies for the sinking of illegal fishing vessels and the impact of these policies on the Malaysian state. International system pressure, state power and other theories were used to help carry out this research. As a result, this study provides an overview of the relationship between Indonesia and Malaysia after the enactment of the policy. First, the Malaysian increase their fish trade and sea safeguard with Indonesia, both in the designated sea area and the gray area. Second, the government of Malaysia adopted the sinking ships method due to its mechanism that is considered effective and efficient in creating detterence effect. Third, both countries agreed to release poor or small fishermen who carry out IUU Fishing made between the President of Indonesia and the Prime Minister of Malaysia.